Sipanundu' Madandan Traditional School as a Cultural Education Space for Preserving Local Wisdom - Gracesika Datu Mangontan; Rahma M; Nurlina Syahrir (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Amid accelerating modernisation and digital globalisation, indigenous communities face mounting pressure to sustain intergenerational cultural transmission. This qualitative single-case study investigates Sipanundu' Madandan Traditional School (Sekolah Adat Sipanundu' Madandan) — a non-formal indigenous learning institution established in Madandan sub-district, Tana Toraja Regency, South Sulawesi, Indonesia — as a cultural education space for preserving Torajan local wisdom. Data were generated through in-depth interviews, participatory observation, and document analysis, and were subjected to interactive analysis (reduction, display, verification) with triangulation to ensure trustworthiness. Findings reveal seven interconnected roles fulfilled by the school: (1) reflective preservation of customary practices; (2) character education grounded in indigenous values; (3) intergenerational transmission of ancestral knowledge; (4) strengthening of Torajan identity; (5) complementary partnership with formal schooling and the church; (6) provision of a community dialogue space; and (7) revitalisation of Torajan language and artistic expression. Seven clusters of local wisdom values are identified as the pedagogical core, including sipanundu' (mutual support), Tallulolona (ecological equilibrium), Sipakaboro' (mutual care), and kada disedan sarong (oral ethical literature). Enabling factors include elder engagement, strong community ownership, and experiential learning methodology; inhibiting factors encompass digital cultural competition, facilitator regeneration urgency, funding constraints, and limited local government recognition. These findings contribute an ethno-pedagogical model demonstrating that community-based indigenous education can serve simultaneously as a mechanism of cultural heritage preservation, character formation, and social cohesion.